2021
DOI: 10.1101/2021.01.06.425587
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TRPM2 ion channels steer neutrophils towards a source of hydrogen peroxide

Abstract: Neutrophils must navigate accurately towards pathogens in order to destroy invaders and thus defend our bodies against infection. Here we show that hydrogen peroxide, a potent neutrophil chemoattractant, guides chemotaxis by activating calcium-permeable TRPM2 ion channels and thus generating an intracellular leading-edge calcium “pulse”. The thermal sensitivity of TRPM2 activation means that chemotaxis towards hydrogen peroxide is strongly promoted by small temperature elevations, suggesting that an important … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…Hence, both CaM and CaMKII play major roles in Ca 2+ signal transduction. Consistent with the previous results (Morad et al, 2021; Wang & Joseph, 2000), H 2 O 2 resulted in a significant increase in the expression of CaM and p‐CaMKII in hAMSCs. Moreover, our data indicated that GA‐D inhibited the production of intracellular ROS (Figure 2d,e), while the expression of CaM and p‐CaMKII was significantly inhibited in H 2 O 2 ‐induced senescent hAMSCs after GA‐D treatment (Figure 3c,d).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Hence, both CaM and CaMKII play major roles in Ca 2+ signal transduction. Consistent with the previous results (Morad et al, 2021; Wang & Joseph, 2000), H 2 O 2 resulted in a significant increase in the expression of CaM and p‐CaMKII in hAMSCs. Moreover, our data indicated that GA‐D inhibited the production of intracellular ROS (Figure 2d,e), while the expression of CaM and p‐CaMKII was significantly inhibited in H 2 O 2 ‐induced senescent hAMSCs after GA‐D treatment (Figure 3c,d).…”
Section: Discussionsupporting
confidence: 92%
“…Ca 2+ homeostasis is disrupted in senescent cells, and the 14‐3‐3ε isoform regulates intracellular Ca 2+ homeostasis by regulating CaM signaling (Russo et al, 2012). In this study, H 2 O 2 was used to stimulate the senescence of hAMSCs through ROS‐caused DNA damage (Jurk et al, 2012; Menon et al, 2013), whereas exogenous H 2 O 2 could also facilitate extracellular calcium influx, causing calcium dysregulation (Morad et al, 2021; Wang & Joseph, 2000). Disruption of intracellular Ca 2+ homeostasis leads to cell senescence (Kim et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This points towards a complex regulation of neutrophil migration by a combination of DUOX2‐dependent and DUOX2‐independent factors secreted by ECs. Although chemokines are clearly important for the recruitment of neutrophils, H 2 O 2 is also a potent neutrophil chemoattractant 53,54 . Notably, DUOX‐derived H 2 O 2 was shown to form a concentration gradient, guiding neutrophil toward the wound in zebrafish and drosophila models 55–58 .…”
Section: Discussionmentioning
confidence: 99%